Access to Home and Community Health Services for Older Adults With Serious, Life-Limiting Illness: A Study Protocol. (January 2021) - Hill, Jacob D.; Cuthel, Allison M.; Grudzen, Corita R.
Objectives: The objective of this study is to identify contextual access factors to home and community health services for end-of-life support for older adults with serious life-limiting illness, as well as determine if access to home and community services is associated with health-care utilization. Design: This study includes an environmental scan, grey literature review, qualitative interviews, and health-care utilization analysis. This study is a subproject of the Grudzen et al. Primary Palliative Care for Emergency Medicine (PRIM-ER) study. Settings/Location: Analysis will include data collection from 17 health systems implementing the PRIM-ER intervention. Participants: For the qualitative interviews, one emergency medicine (EM) physician and one EM nurse will be interviewed from each of the 17 participating health systems. For the health-care utilization analysis, we will use the Senior Care Services Scale (SCSS), American Hospital Association Annual Survey of Hospitals (AHA-ASH), and Medicare claims for all emergency department (ED) visits for serious illness who present at each participating health system. Outcome Measures: The contextual analysis will obtain data on home and community services, such as hospice, home health services, assisted living, integrative medicine services, etc., available around each health system's highest volume ED, federal and state regulations influencing access to services, as well as EM provider perspectives on access to services. The health-care utilization analysis will determine if SCSS scores, which measure service availability, are associated with health-care usage. High or low SCSS scores are determined by comparing health system service availability on the AHA-ASH to the national median SCSS value.